Toward the use of mixed microbial cultures for the biological production of adipic and levulinic acid - Pinto-Ibieta, Fernanda; Cea, Mara; Serrano, Antonio; Felissia, Fernando E.; Area, María Cristina; Cabrera, Francisco; Ciudad, Gustavo (Frontiers in Microbiology, 2023)
Biological synthesis of high added-value compounds like adipic acid (AA), levulinic acid (LA), or polyhydroxybutyrate (PHB) using pure culture has been reported separately. However, pure culture requires sterile conditions and the use of specific carbon sources, resulting in high operating costs. Different alternatives based on the use of mixed microbial cultures (MMC) have been explored to resolve this problem. MMC have been widely reported for the production of PHB, but scarcely reported for LA production and never for AA synthesis. This work presents a novel strategy for the co-production of AA LA, and PHB using MMC. The strategy consists in selecting a MMC producer of AA, LA and PHB from an inoculum obtained from a wastewater treatment plant, which is then subjected to the feast and famine culture strategy in a sequential batch reactor, coupled with a batch reactor step to enhance the accumulation of AA and LA. The results showed that the MMC could produce 16±2, 23±1 and 5% (g compound/g volatile solids/w) of AA, LA and PHB respectively, using a non-fermented residual biomass rich in pentose, namely synthetic hemicellulose hydrolysate (SHH), as the carbon source. These results contribute to generating future research to better understand and optimise the biosynthesis of these compounds by MMC.